2015
DOI: 10.1016/j.egypro.2015.03.230
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Dye Sensitized Solar Cells with Spray Coated Carbon Nano Tube (CNT) Based Counter Electrodes

Abstract: In this paper, dye-sensitized solar cells (DSSC) have been fabricated on fluorine-tin-oxide (FTO) glass substrates, in which TiO 2 electrodes have been printed and multi-walled carbon nanotubes (CNT) counter electrodes have been spray-coated. Ruthenium based dye (C 58 H 86 N 8 O 8 RuS 2 ) has been used as photosensitizer, and the cell was constructed by stacking the dye-sensitized TiO2 on CNT counter electrodes using Surlyn sheet of 50 μm thick as a spacer. The electrolyte containing I-/I3-redox couple was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Along with basic electron transfer processes in DSSC prospects of a state-of-art device based on dye adsorbed on TiO 2 and I -/I 3in the form of redox pairs electrolyte is shown in Figure 1(a). On illumination, an electron photo generated by dye molecules as like in photosynthesis [19]. By photon (hυ) absorption a dye molecule is excited whereas electron is excited from HOMO into LUMO subsequently, the free electron is injected into the TiO 2 conduction band and left the oxidized dye molecule.…”
Section: Methodsmentioning
confidence: 99%
“…Along with basic electron transfer processes in DSSC prospects of a state-of-art device based on dye adsorbed on TiO 2 and I -/I 3in the form of redox pairs electrolyte is shown in Figure 1(a). On illumination, an electron photo generated by dye molecules as like in photosynthesis [19]. By photon (hυ) absorption a dye molecule is excited whereas electron is excited from HOMO into LUMO subsequently, the free electron is injected into the TiO 2 conduction band and left the oxidized dye molecule.…”
Section: Methodsmentioning
confidence: 99%
“…The working electrode consists of transparent conductive glass such as Indium Tin Oxide (ITO) or Fluorine Tin. Oxide (FTO), nanocrystalline TiO2 semiconductor coating, and dye Counter electrode consists of transparent conductive glass that has been coated with carbon [8] or platinum [9]. The electrolyte used is an iodine trioxides electrolyte with a pair redox (I -/ I3 -).…”
Section: Introductionmentioning
confidence: 99%
“…Ramasamy et al fabricated spray-coated MWCNT counter electrode and showed the effect of spray time/coating thickness[41]. Widodo also fabricated spray-coated CNT on FTO glass substrate for counter electrode for DSSC[42]. Prasetio et al used different weight (0.01, 0.02 and 0.04 gram) of CNT and observed the cell performance of DSSC[43].…”
mentioning
confidence: 99%